Desain dan Implementasi Deteksi WebShell Malicious Web Shell (Backdoor Trap) - Raditya Faisal Waliulu; Santrinita Trhessya Jumame (Universitas Diponegoro, 2020)
We present a report on hacker attacks against production servers on increased PHP vulnerabilities through SQL Injection attacks, XSS (Cross Site-Scripting), Cookie hijack, miss configuration, social engineering, CSRF (cross site request forgery), OTP bypass (take over account) and others. Hacker attacks leave a backdoor or webshell that will be accessed remotely (remote), this is common in blackhat hackers. Provides a shelltrap framework to use for and perform and clean the backdoor on the server. Because the back door has characteristics, namely: (1) taking over the physical server or localrooting; (2) adaptation to the run time environment; (3) using global variables to access the server. Have evaluated shelltrap on realworld server tame PHP Script and PHP backdoor. The experimental results get high level detection results of 98 %.